(x + 9)(x + 2)
x2 -11x-12= (x-12)(x+1)
The LCM is the absolute value of x.
x2 = -11x - 10 x2 + 11x + 10 = 0 (x + 1)(x + 10) = 0
If you mean x2+11x+24 then it is (x+3)(x+8) when factored
(x + 9)(x + 2)
It is (x+2)(x+9) when factored
The actual equation itself is the polynomial. There is no polynomial for it, and your question doesn't really make sense.
x2 -11x-12= (x-12)(x+1)
X2 -11x +10=(x - 1 )(x - 10)
3x2 + 33x + 54 =3(x2 + 11x + 18) = 3(x + 9)(x + 2)
Do you mean x2+11x-26 if so then it is (x-2)(x+13) when factored
Divide all terms by -1 so: x2-11x-26 = (x+2)(x-13) when factored
-(x + 13)(x - 2)
-x2 - 11x + 26 = -(x2 + 11x - 26) = -(x2 - 2x + 13x - 26) = -[ x(x - 2) + 13(x - 2) ] = -(x + 13)(x - 2) = (x + 13)(2 - x)
If you meant to write -x2 - 11x + 26, that factors to -(x - 2)(x + 13)
12